Large Group Instruction in Elementary Accounting. - McCormick, Frank L.; Churchill, Neil C. (The Accounting Review, 1967)
This article focuses on a study which discussed the views of accounting professors on the problem of efficient utilization of faculty in the teaching of elementary accounting. The need for more efficient utilization of the teaching staff is a pressing problem today with mounting enrollments and a continuing shortage of qualified accounting professors. Some universities have kept their elementary accounting sections small by staffing them with graduate assistants. Other schools schedule large lecture-hall sections taught be regular faculty members. Others reach a large number of students with a single professor via television. The author conducted a study in which thirty-two leading accounting professors presented their views on the problem of more efficient utilization of faculty in the teaching of elementary accounting. The conflict inherent in large group instruction between the necessity of providing instruction to large numbers of students and the desirability of close personal contact between instructor and students is unresolved.